PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN LITERASI SAINS SISWA DI SMPN 11 SURABAYA - Ali Akbar; An Nuril Maulida Fauziah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze improvements in students’ science literacy following the implementation of the discovery learning model. The research design used is a pre-experimental design, specifically a one-group pretest-posttest design. The research subjects were students in class IX-G at SMPN 11 Surabaya. The research instruments used were pretests and posttests. The data analysis techniques used were the normality test, t-test, and N-Gain test. The average N-Gain score obtained was 0.50, which falls into the moderate improvement category. Meanwhile, the N-Gain percentage for all students showed that 11% of students experienced improvement in the high category. A total of 75% showed moderate improvement. Meanwhile, the remaining 14% of students had low N-Gain scores. Thus, it can be concluded that the application of the discovery learning model can improve students’ science literacy. A suggestion for future research is that this model could be applied to different subject materials or educational levels.